Purchase Decision Making Model Based on Mental Accounting in The Day-Old Chicken Industry in Indonesia - Jatmiko; mudjiarto; Aidil Fadli, Jul; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
The process of purchasing decisions essentially goes through 5 stages, starting from the introduction of problems, information search, alternative evaluations, purchasing decisions, and post-purchase behavior. Research findings show that Industry of Day-Old Chicken (DOC), after passing through the evaluation phase of an alternative, customer does not directly make a purchasing decision, but through Mental Accounting to maximize its financial utility. Mental Accounting actions arise in purchasing decisions because the involvement of external factors plays a role in influencing the level of investment risk, at the product level or the level of high involvement price industry, the purchasing decision is through careful consideration. Customer behavior shows an improvement in the theory of the stages of the previous purchase decision from 5 stages changed to 6 stages, Mental Accounting fills the position of the fourth stage and then the purchase decision.